Adverse Childhood Experiences and Healthcare Costs in Adult Life. Issue 5 (4th July 2019) - Loxton, Deborah; Townsend, Natalie; Dolja-Gore, Xenia; Forder, Peta; Coles, Jan
ABSTRACT: The current study aims to present the prevalence of adverse childhood experiences and examine the healthcare costs associated with primary, allied, and specialist healthcare services. The Australian Longitudinal Study on Women's Health is a general health survey of four nationally representative age cohorts. The current study uses 20 years of survey and administrative data (1996–2015) from the cohort born 1973–1978. Overall, 41% of women indicated at least one category of childhood adversity. The most commonly reported type of childhood adversity was having a household member with a mental illness (16%), with the most commonly reported ACES category being psychological abuse (17%). Women who had experienced adversity in childhood had higher healthcare costs than women who had not experienced adversity. The healthcare costs associated with experiences of adversity in childhood fully justify a comprehensive policy and practice review.